2020
DOI: 10.1186/s41205-020-00087-0
|View full text |Cite
|
Sign up to set email alerts
|

3D - Printed Patient Specific Instrumentation in Corrective Osteotomy of the Femur and Pelvis: A Review of the Literature

Abstract: Background The paediatric patient population has considerable variation in anatomy. The use of Computed Tomography (CT)-based digital models to design three-dimensionally printed patient specific instrumentation (PSI) has recently been applied for correction of deformity in orthopedic surgery. This review sought to determine the existing application of this technology currently in use within paediatric orthopaedics, and assess the potential benefits that this may provide to patients and surgeons. Methods A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Inclusion criteria used in the current study included: (1) randomised controlled trials (RCTs); (2) research for traumatic fractures of limbs and pelvis, regardless of exact cause of injury; (3) 3D fracture models were used for preoperative plan to determine where it best secured fracture fragments, suitable metal plates and screws with ideal location, length and orientation; (4) comparing efficacy of 3D-printed assisted surgery with conventional surgery, without 3D printing model, for traumatic fractures; (5)…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusion criteria used in the current study included: (1) randomised controlled trials (RCTs); (2) research for traumatic fractures of limbs and pelvis, regardless of exact cause of injury; (3) 3D fracture models were used for preoperative plan to determine where it best secured fracture fragments, suitable metal plates and screws with ideal location, length and orientation; (4) comparing efficacy of 3D-printed assisted surgery with conventional surgery, without 3D printing model, for traumatic fractures; (5)…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Previous studies have reported that insufficient understanding of fractures may also increase surgical invasiveness in order to sufficiently expose fracture sites during operation to understand the fracture circumstance. This aggravates tissue damage, prolongs operation time and increases intraoperative blood loss ( 5 ). Therefore, therapeutic effects of traditional surgery are unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside reduced radiation exposure and shortened surgery time, Shi et al [ 34 ] also showed improved accuracy using 3D planning and PSI compared to conventional techniques in children with proximal femoral corrective osteotomy in developmental dysplasia of the hip. In a review, Baraza et al [ 20 ] similarly stated improved accuracy in corrective femoral osteotomies using 3D planning and PSI compared to conventional techniques. The improved accuracy probably is a result of the assistance of the PSI, enabling the surgeon in a precise execution of the preoperative planning into the intraoperative situation.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al [ 19 ] previously described the application of 3D-printed navigation templates for locking compression pediatric hip plates (LCP-PHP) in children with femoral neck fractures or hip dysplasia. A recent literature review of Baraza et al [ 20 ] summarized improved accuracy and decreased procedure times in corrective osteotomies of the femur by the application of PSI compared to conventional methods. Overall, an increasing trend of the implementation of 3D planning and the use of PSI at the proximal femur can be observed.…”
Section: Introductionmentioning
confidence: 99%